(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazione SOMMARIO: 1. Evoluzione del diritto dell’Unione europea. La tutela dei diritti fondamentali – 2. Il fenomeno religioso – 3. I rapporti delle organizzazioni religiose, filosofiche e non confessionali con l’Unione europea nell’art. 17 TFUE – 4. Il dialogo tra teoria, prassi e limiti di competenza dell’Unione. ABSTRACT: The essay analyzes the European Union law development relating to fundamental rights and religious freedom. In particular, it deepens the relationship between EU and religious, philosophical and non-confessional organisations, in the light of changes introduced by the Lisbon Treaty. By art. 17 TFEU, the European Union formalized its commitment to maintain an open, transparent and regular dialogue with these churches and organisations. The author performs some thoughts on the practical application of the provision, outlining developments and critical issues, with reference to the limited competence of the European Union, pursuant to art. 17 TFEU par. 1-2.